Transgenic organisms (chimeras) and their Islamic evaluation - Bouzenita, Anke Sandra; Mirghani, Mohamed Elwathig Saeed (Sci.Int.(Lahore), 2014)
The production of transgenic organisms starts by isolation of the gene of interest from the genome of a gene-donor species (Animal or plant or microorganism). The isolated gene is usually altered to be fit to function effectively in a host organism (usually microorganism). That gene is to be combined with other genes to prepare it to be introduced into another organism; at that point it is known as a trans-gene. A transgenic organism, sometimes called a chimera. Chimeras contain transgenes introduced by technological methods rather than through selective breeding. The production of chimeras, either combining DNA of different animal species or combining animal/human origin DNA; does it constitute a prohibited change of creation? Is there a difference between mating animals of related species (like horse and donkey, tiger and lion) which may occasionally occur naturally, and those of totally different species (mouse and frog, dog and cow)? What is the distinguishing guideline between permissible and prohibited? And what would you consider a chimera? Are the cells you have on a petri dish already a chimera, or is it the complete being? What would be the rationale of bringing a chimera about? Is there ANY shar’i objective involved, or is it just playing with creation (‘abth) or does it happen for material benefit?